The Effectiveness of Natural Environment Teaching in Improving Early Numeracy Skills in Children with Autism Spectrum Disorder in Inclusive Elementary Schools: A Single Subject Research Study - Tri Gunadi (Eduvest - Journal of Universal Studies, 2026)
This study aimed to evaluate the effectiveness of Natural Environment Teaching (NET) in improving early numeracy skills among children with Autism Spectrum Disorder (ASD) in inclusive elementary school settings. Early numeracy is a fundamental academic prerequisite that is often impaired in children with ASD due to core deficits in communication, cognitive flexibility, and generalization. This study employed a quantitative approach using a Single Subject Research (SSR) design with a multiple baseline across participants. Three children with ASD (DSM-5 Level 1–2), aged 6–8 years and enrolled in inclusive elementary schools, participated in the study. The intervention was conducted over 12 sessions (approximately 30–45 minutes each), integrating numeracy learning into natural classroom activities. Data were collected through direct observation and frequency recording and analyzed using visual analysis and the Percentage of Non-Overlapping Data (PND) method. Interobserver agreement (IOA) averaged 92.3%, while implementation fidelity averaged 91.7%. The results revealed consistent improvement across all participants, from baseline phases (mean 21.7%–31.7%) to intervention phases (57.5%–63.8%), with PND scores ranging from 90%–100%, indicating a highly effective intervention. Skill maintenance was observed at 72.5%–82.5%, demonstrating strong learning retention. These findings confirm that NET is an effective and ecologically valid naturalistic instructional approach for improving numeracy skills in children with ASD in inclusive educational settings.